Analisis Peran Guru dalam Meningkatkan Minat Baca pada Siswa Sekolah Dasar - Andini, Amelia; Nisa, Sahrun; Suriani, Ari (Lembaga Yasin AlSys, 2024)
This study investigates the role of teachers in encouraging children's interest in reading through learning support, various approaches, and variables that influence interest in reading. The SLR (Systematic Literature Review) method was used, which evaluated nine articles from nationally recognized journals. The research results show that teachers help, encourage, evaluate and encourage students' interest in reading. The use of classroom libraries, wall journals, and interesting textbooks can stimulate students' interest in reading. In addition, internal variables such as students' reading ability and comprehension as well as external variables such as the environment, resources and availability of reading materials also influence students' interest in reading. Therefore, teachers must work hard to choose the most suitable learning methods and media.